A simple oxidation technique for quantum dot dimension shrinkage and tunnel barriers generation - Madnarski Sutikno; Uda, Hashim, Prof. Dr.; Zul Azhar, Zahid Jamal, Prof. Dr. (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com